Investigation of the First Seven Reported Cases of Candida auris, a Globally Emerging Invasive, Multidrug‐Resistant Fungus—United States, May 2013–August 2016. Issue 1 (28th December 2016) - Vallabhaneni, S.; Kallen, A.; Tsay, S.; Chow, N.; Welsh, R.; Kerins, J.; Kemble, S. K.; Pacilli, M.; Black, S. R.; Landon, E.; Ridgway, J.; Palmore, T. N.; et al.
Abstract : November 11, 2016/65(44);1234–1237. What is already known about this topic? Candida auris is an emerging pathogenic fungus that has been reported from at least a dozen countries on four continents during 2009–2015. The organism is difficult to identify using traditional biochemical methods, some isolates have been found to be resistant to all three major classes of antifungal medications, and C. auris has caused health care–associated outbreaks. What is added by this report? This is the first description of C. auris cases in the United States. C. auris appears to have emerged in the United States only in the last few years, and U.S. isolates are related to isolates from South America and South Asia. Evidence from U.S. case investigations suggests likely transmission of the organism occurred in health care settings. What are the implications for public health practice? It is important that U.S. laboratories accurately identify C. auris and for health care facilities to implement recommended infection control practices to prevent the spread of C. auris . Local and state health departments and CDC should be notified of possible cases of C. auris and of isolates of C. haemulonii and Candida spp. that cannot be identified after routine testing. Abstract : This report details the first U.S. cases of a new fungal infection seen primarily in immunocompromised hosts, including stem cell transplant recipients.